Supraomohyoid neck dissection in early carcinoma of oral cavity with clinically N0 neck: A case series (Indian Journal of Case Reports, 2026)
Management of clinically N0 neck in early-stage oral squamous cell carcinoma (OSCC) remains controversial. Supraomohyoid neck dissection (SOHND) has emerged as an effective surgical technique for the elective treatment of cervical lymph nodes while minimizing functional morbidity. This case series evaluates the clinical outcomes, complications, and short-term prognosis of SOHND in early-stage oral cavity carcinoma patients with clinically negative neck nodes (N0). Five male patients with early-stage OSCC and clinically N0 neck underwent SOHND with primary tumor resection between December 2022 and February 2025. All patients had significant tobacco history (4–5 years). Surgical procedures involved lymph node clearance from Level I to Level III through a transverse horizontal neck incision. Patients were followed for 1.5 years without adjuvant radiotherapy or chemotherapy. All surgeries were completed without major intraoperative complications. Histopathological examination confirmed squamous cell carcinoma in all cases. No patients showed clinical signs of recurrence during the 1.5-year follow-up period. All patients experienced temporary speech difficulties that resolved with simple speech therapy. One patient developed a mucocele at 9 months, which resolved spontaneously. Neck scar contraction was observed in all cases without significant functional limitations. SOHND appears to be an effective and safe method for managing early-stage OSCC in clinically N0 patients, achieving satisfactory oncologic control while preserving function and minimizing surgical morbidity.